ANALISIS KINERJA PELAYANAN PUBLIK DI KANTOR CAMAT SANGKULIRANG KABUPATEN KUTAI TIMUR - Marjoni Rachman Rika Ardina (ADMINISTRASI PUBLIK, 2017)
RIKA ARDINA. Public Service Performance Analysis at Sangkulirang District Office of East Kutai Regency, under the guidance of Dr. Marjoni Rachman, M.Si as Supervisor I and Drs. Ghufron, M.Si as Supervisor II.This study aims to find and describe the Performance of Public Service in the Office of the Sub-district of Sangkulirang, East Kutai Regency. The approach used in this research is qualitative descriptive approach. In this research will be description of four indicators, namely Accountability, Reponsiveness, Competency and Transparency.The results showed that Public Service Performance at Sangkulirang District Office of East Kutai Regency got a score of 88.4% and this was included in either category. Thus the formulation of the problem in this study has been answered.